TYPES OF INFORMATION (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: This article explores the various types of information, including factual, conceptual, procedural, emotional, behavioral, and motivational information. Each type serves a unique purpose and plays a critical role in various domains, such as education, decision-making, communication, and personal development. The article provides examples for each type, highlights their significance, and discusses how they impact human understanding and behavior. The aim is to emphasize the diversity of information and its crucial role in shaping actions, attitudes, and knowledge.